MEMINIMALISIR ASIMETRI INFORMASI MELALUI LAPORAN KEUANGAN (STUDI LITERATUR) - Idzharotun, Luklu'ul; Ni'mati Rahmatika, Arivatu; Widyaningsih, Bekti (Izdihar: Jurnal Ekonomi Syariah, 2024)
ABSTRACT This study aims to find out how to minimize information asymmetry financial repots. Information asymmetry can cause imbalance in economic decision making and reduce marke efficiency. The design of this research study with the analytical method used in the form of content analysis. This study analyses various aspects of financial repots that contribute to reducing information uncertainty, such as auditor independence, audit quality and information transparency. The results of this study show that transparent, accurate and consistent financial reports play an important role in increasing stakeholder trust and reducing risks related to information asymmetry. Based on the result of this study, it confirm the importance of good accounting policies and practices in creating a more transparent and fair business environment.